KOMPARASI VISUAL PROPERTI KESENIAN KUDA LUMPING DI KAMPUNG SIDOSARI DESA CIPANAS KECAMATAN CIPATUJAH KABUPATEN TASIKMALAYA DENGAN KUDA LUMPING DI KAMPUNG KEBON WARU DESA GUNUNG BATU KECAMATAN CIRACAP KABUPATEN SUKABUMI - Dais Ersyka Endang; Wan Ridwan Husen; Asep Wasta (Prodi Pendidikan Sendratasik FKIP UMTAS, 2021)
In Cipatujah Subdistrict Tasikmalaya Regency, to be precise in sidosari Village, Cipanas Village, there is a Kuda Lumping art group. The existence of this art group is a cultural asset that must be fully appreciated and its existence be maintained, considering that cuurently the Kuda Lumping art is rarely recognized and rarely found. In teh research process the author found a thesis that examines the visual properties of Kuda Lumping art in Kebon Waru Village, Gunung Batu Village, Ciracap District, Sukabumi District. On this occasion the author will make comparisons regarding matters relating to the art of the Kuda Lumping that is in Sidosari Village Cipanas Village Cipatujah District Tasilmalaya District with Kebon Waru Village Gunung Batu Village Ciracap District Sukabumi District, reveal and analyze in the form of how to visualize the costume accessories and properties in the two places. This reseach uses qualitative methods with a descriptive approach. Data collection in this study using interviews, documentationn and literature studies that are covered by using instruments or tools such as cameras, cellphones, and writing instruments. The object under study is the art of Kuda Lumping. The results of this study are expected to provide insight to the public regarding the visualization of the art properties of the Kuda Lumping art.